Solitons with isospin - Gomes, J. F.; Sotkov, G. M.; Zimerman, A. H. (Elsevier B.V., 2005)
We study the symmetries of the soliton spectrum of a pair of T-dual integrable models, invariant under global SL(2)(q) circle times U(1) transformations. They represent an integrable perturbation of the reduced Gepner parafermions, based on certain gauged SL(3)-WZW model. Their (semiclassical) topological soliton solutions, carrying isospin and belonging to the root of unity representations of q-deformed SU(2)(q)-algebra are obtained. We derive the semiclassical particle spectrum of these models, which is further used to prove their T-duality properties. (c) 2005 Elsevier B.V All rights reserved.